Calculus (3rd Edition)

Published by W. H. Freeman
ISBN 10: 1464125260
ISBN 13: 978-1-46412-526-3

Chapter 3 - Differentiation - 3.3 Product and Quotient Rules - Exercises: 7

Answer

$f’(x) =- \frac{2}{(x-2)^{2}}$

Work Step by Step

$f(x) = \frac{x}{x-2} $ $Quotient$ $Rule:$ $f’(x) = \frac{(x-2)\frac{d}{dx}(x)-(x)\frac{d}{dx}(x-2)}{(x-2)^{2}}$ $f’(x) = \frac{(x-2)-(x)}{(x-2)^{2}}$ $f’(x) =- \frac{2}{(x-2)^{2}}$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.